Diversité, variabilité, connectivité : Mobiliser les savoirs locaux pour cultiver la biodiversité - Renzo d’Alessandro; Thierry Linck (Développement Durable et Territoires)
At all relevant scales, biodiversity refers to diversity and adaptability properties and requires genes circulation and sharing. This remains true regarding cultivated biodiversity, providing that knowledge, which circulates with the genes, has similar properties.In Tenejapa, in Chiapas Mountains, maize seeds circulation is the key to collective construction and appropriation of life and knowledge. The shared possession of knowledge and nature is radically contrary to the individual and exclusive appropriations that characterize the dominant agro-food system. Similarly, cultivated biodiversity relies on temporal and spatial patterns contrary to those of seed certification.Seeds peasant movements are based on similar values. It also evidences the limits of knowledge hybridization needed to cope with the erosion of biodiversity.